2017
DOI: 10.3389/fchem.2017.00046
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Products of Linalool and Modulation of GABAA Receptors

Abstract: Terpenoids are major subcomponents in aroma substances which harbor sedative physiological potential. We have demonstrated that various monoterpenoids such as the acyclic linalool enhance GABAergic currents in an allosteric manner in vitro upon overexpression of inhibitory α1β2 GABAA receptors in various expression systems. However, in plants or humans, i.e., following intake via inhalation or ingestion, linalool undergoes metabolic modifications including oxygenation and acetylation, which may affect the modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 40 publications
(69 reference statements)
1
20
0
2
Order By: Relevance
“…9, 10 and 12 showed that flumazenil reversed the pharmacological response of EO in some important behavioral parameters, suggesting the possible involvement of GABA A receptors. These findings are in agreement with several pharmacological reports demonstrating that the sedative and anxiolytic potential of monoterpenes and sesquiterpenes appears to be mediated by GABA/benzodiazepine transmission (Granger et al, 2005;Rivera et al, 2014;Milanos et al, 2017;Sousa et al, 2015). Additionally, EO promoted no alteration in the motor coordination of the animals, being considered a satisfactory candidate for the development of new herbal medicines acting on CNS disorders.…”
Section: Discussionsupporting
confidence: 92%
“…9, 10 and 12 showed that flumazenil reversed the pharmacological response of EO in some important behavioral parameters, suggesting the possible involvement of GABA A receptors. These findings are in agreement with several pharmacological reports demonstrating that the sedative and anxiolytic potential of monoterpenes and sesquiterpenes appears to be mediated by GABA/benzodiazepine transmission (Granger et al, 2005;Rivera et al, 2014;Milanos et al, 2017;Sousa et al, 2015). Additionally, EO promoted no alteration in the motor coordination of the animals, being considered a satisfactory candidate for the development of new herbal medicines acting on CNS disorders.…”
Section: Discussionsupporting
confidence: 92%
“…Recent research showed that 3-Carene had sedative and analgesic, digestion and analgesic, antimicrobial effects. [19] Sinem Milanos [20] on the metabolism of Linalool and Linalool the regulation process has been studied and the results confirm that Linalool is well-known for its calming effect in the field of medicine. β-Pinene has obvious antibacterial activity in vitro [21], and Caryophyllene also has strong bacteriostatic action [22].…”
Section: Resultsmentioning
confidence: 76%
“…All 5 studies used aromatherapy with lavender essential oil in patients with cardiovascular diseases. 12,[15][16][17][18] The studies were published from 1992 to 2020. The sample size ranged from 60 to 135 patients, 15,17 and the mean age was 60 to 73 years.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 60 to 135 patients, 15,17 and the mean age was 60 to 73 years. 16,17 Three studies 12,15,16 included participants of both sexes, and 2 studies 17,18 included only women. Regarding the participants, 2 studies with reflexology (technique that stimulates different points on the feet).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation